Book Review: Iron Age Experience, Iron Age Kids and Kaptol - Hallstatt Food Workshop and Cookbook - Caroline Nicolay (EXARC, 2020)
Iron-Age-Danube was a cross-border project, part of the Interreg Danube Transnational Programme of the European Union. It lasted from 2017 until 2019. It counted 12 partners and seven associated organisations from in Austria, Croatia, Hungary, Slovakia and Slovenia. The major goal of the project is to communicate a lively image of archaeological research and the Iron Age landscapes to the visitors and to raise the awareness for the importance of archaeological monuments for the human history. Another goal is the protection of the monuments and landscapes as well as their sustainable use for the tourism. For communication purposes, several booklets were produced, available as free PDF downloads.